2012
DOI: 10.1177/1352458512458009
|View full text |Cite
|
Sign up to set email alerts
|

Severe multiple sclerosis reactivation under fingolimod 3 months after natalizumab withdrawal

Abstract: We report the case of a woman with multiple sclerosis who developed a severe neurological condition following natalizumab (NZB) withdrawal and soon after fingolimod (FTY) initiation. FTY was started 3.5 months after a two-year NZB treatment. Fifteen days later, she suffered partial repetitive seizures followed by a tonicoclonic seizure. This was associated with attention difficulties and an increased asthenia. Brain MRI follow-up disclosed large demyelinating active lesions in favour of disease reactivation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…Interestingly, ablation of the RMS with ARA-c also impeded cell egress from the CNS, perhaps identifying a role for immune cell trafficking along the RMS in the resolution of CNS inflammation. The accumulation of inflammatory cells and the prevention of their egress in the continued inflammation associated with active MS plaques may provide an explanation for the increasing numbers of adverse events associated with fingolimod treatment in MS (45). However, the identity of the inflammatory cell(s) that might be detrimental in this context is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ablation of the RMS with ARA-c also impeded cell egress from the CNS, perhaps identifying a role for immune cell trafficking along the RMS in the resolution of CNS inflammation. The accumulation of inflammatory cells and the prevention of their egress in the continued inflammation associated with active MS plaques may provide an explanation for the increasing numbers of adverse events associated with fingolimod treatment in MS (45). However, the identity of the inflammatory cell(s) that might be detrimental in this context is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The only available data derive from case reports and observational studies on MS patients who switched from natalizumab to fingolimod, generally showing a disease reactivation after the switch with few exceptions [16,17,18,19,20,21]. It has been suggested that early fingolimod start (i.e., before the end of the recommended natalizumab 3-month washout interval) might prevent relapse occurrence [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Rinaldi et al observed that, in a cohort of 22 patients exposed to NAT and subsequently treated with FTY after a washout period of three months, the rate of clinical and/or radiological relapses was 31.8% during the first month of therapy and that there was a rebound in 14% of patients in the first nine months of therapy [19]. There are several other reports of clinical and radiological relapses after NAT discontinuation despite treatment with FTY after at least three months of washout [20,21,22,23]. Havla et al compared a cohort of 26 patients previously exposed to NAT and subsequently treated with FTY with a cohort of 10 patients who received no immunomodulatory treatment after discontinuation of NAT and found a significant decrease in the median ARR after NAT (0.0 vs. 1.5) and in the number of patients with gadolinium-enhancing lesions (9 vs. 67%) [24].…”
Section: Discussionmentioning
confidence: 99%